Diseño de una matriz de decisión para la ejecución de operaciones de pesca en pozos inyectores del campo La Cira Infantas (2017)
In the present project a decision matrix for the fishing operations in the injectors with the selective selections of the Field La Cira Infantas is made in order to reduce the non-operative times caused by the decision making at the moment of the operation, will have in has a statistical analysis of results from the wells worked in Campaign 40K and the critical parameters of wrapping, field area to intervene, Run Life and number of wedge packings installed in the strings. Based on the critical parameters and the statistical analysis, the decision matrix calculates the estimated time in days that a fishing operation takes in the field and presents a series of recommendations to reduce the time it takes the work.